1993
DOI: 10.1016/0378-1097(93)90608-5
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between umuC induction and Salmonella mutagenicity assay for quinolone antimicrobial agents

Abstract: Quinolone antimicrobial agents induce the SOS response in bacteria, including the umuDC genes necessary for error-prone repair. Consequently these drugs may be mutagenic in bacteria with a functional SOS response. Differential killing tests with Escherichia coli WP2 (trp) and its repair-deficient derivative CM871 (trp lexA recA uvrA) indicated that a functional DNA repair system was protective against the action of quinolones, implying that quinolones are causing some form of DNA damage (not necessarily direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…The preparation and characterization of the drug-metal complexes and evaluation (Sadeek et al 2011;Power and Phillips 1993) of the biological activity have gained significance. According to chelation theory, chelation enhances the biological activity of metal complexes by increasing the complexity.…”
mentioning
confidence: 99%
“…The preparation and characterization of the drug-metal complexes and evaluation (Sadeek et al 2011;Power and Phillips 1993) of the biological activity have gained significance. According to chelation theory, chelation enhances the biological activity of metal complexes by increasing the complexity.…”
mentioning
confidence: 99%
“…2 Many studies have shown that nalidixic acid and older quinolones stimulate some of the genes involved in the bacterial SOS stress response as sequelae of cellular DNA damage. [3][4][5] As a continuation of our interest in bacterial responses to subinhibitory levels of small molecules, we show here that sub-MIC levels of older and newer FQs induce significant transcriptional responses in S. enterica serovar Typhimurium (S. typhimurium) ATCC strain 14028. The genes modulated by these antimicrobials are not only strongly associated with bacterial stress functions but also influence virulence and metabolism.…”
Section: Introductionmentioning
confidence: 69%
“…DNA damage created by quinolone antibiotics has been shown to be sufficient to stimulate umuC transcription and the SOS response. 4,5 The initial response to DNA damage is the reduction in LexA protein levels and induction of LexA repressed genes, which include lexA, umuDC and dinP. 2,3 (In Escherichia.…”
Section: Fq-responsive Promoters Involved In Stress Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Quinolones have been reported to induce SOS response and mutation through an error-prone repair pathway (Phillips et al, 1987;Clerch et al, 1992;Power and Phillips, 1993;Albertini et al, 1995). Both S. typhimurium TA102 and E. coli WP2uvrA/pKM101 have plasmid pKM101 containing a set of mucA and B genes, which are analogs of SOS umuD and C genes, and therefore the mutagenicity of the quinolones observed in the previous study is expected to be induced through errorprone repair by the plasmid pKM101.…”
Section: Introductionmentioning
confidence: 81%